2015
DOI: 10.1007/s00247-015-3419-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of early and late MRI in neonatal hypoxic–ischemic encephalopathy using three assessment methods

Abstract: Early MRI may provide valuable information about brain injury to help parents and neonatologists in intensive-care decisions at the end of hypothermia treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 47 publications
1
21
0
1
Order By: Relevance
“…In this study, we confirmed that early MRI had a predictive value at least as good as late MRI, as was expected given the excellent agreement between early and late MRIs [8][9][10][11]. Our results were inconsistent with the results of a meta-analysis which suggested that the discriminatory power of late MRI (days 8-30) was higher than that In our study, the ADC measurements added little to the visual analysis as a prognostic tool.…”
Section: Discussionsupporting
confidence: 67%
See 3 more Smart Citations
“…In this study, we confirmed that early MRI had a predictive value at least as good as late MRI, as was expected given the excellent agreement between early and late MRIs [8][9][10][11]. Our results were inconsistent with the results of a meta-analysis which suggested that the discriminatory power of late MRI (days 8-30) was higher than that In our study, the ADC measurements added little to the visual analysis as a prognostic tool.…”
Section: Discussionsupporting
confidence: 67%
“…Yet, the median time to follow-up remained within our limit of two years of age. There were also some technical limitations previously identified, particularly as we used two different coils with different parameters for T1-weighted imaging [11].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Rather than being a real prognostic tool, it helps to the interpretation of subtle findings when clear pathological patterns are not evident. This is the same for the discussed “prognostic” value of signal changes in the posterior limb of the internal capsule (PLIC) [ 103 ].…”
Section: Assessment Of Timing Of the Onsetmentioning
confidence: 66%